2019
DOI: 10.1128/msphere.00002-19
|View full text |Cite
|
Sign up to set email alerts
|

A CRISPR Interference Platform for Efficient Genetic Repression in Candida albicans

Abstract: Fungal pathogens are an increasingly important cause of human disease and mortality, and Candida albicans is among the most common causes of fungal disease. Studying this important fungal pathogen requires a comprehensive genetic toolkit to establish how different genetic factors play roles in the biology and virulence of this pathogen. Here, we developed a CRISPR-based genetic regulation platform to achieve targeted repression of C. albicans genes. This CRISPR interference (CRISPRi) technology exploits a nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 87 publications
0
64
0
Order By: Relevance
“…Gilbert et al compared different repressive effector domains, including the KRAB (Krüppel associated box) domain, the WRPW domain and the CS (Chromo Shadow) domain, and found that dCas9-KRAB was the best repressor when targeting to a window of -50 to +300 bp relative to the transcription start site (TSS), or 0–100 bp region just downstream of the TSS ( Figure 3C ; Gilbert et al, 2013 , 2014 ). Another dCas9 fusion domain, Mxi1, a mammalian transcriptional repressor domain that is reported to interact with the histone deacetylase Sin3 homolog in yeast, also showed effective repression in yeast ( Gilbert et al, 2013 ; Jensen et al, 2017 ; Schwartz et al, 2017 ; Geller et al, 2019 ; Wensing et al, 2019 ). In another research, KRAB was fused to RNA-binding domains (COM-KRAB) and achieved similar repression effects when targeting DNA sites overlapped the TSS using a scaffold RNA (scRNA) ( Figure 3D ; Zalatan et al, 2015 ).…”
Section: Regulation Of Gene Expression By Crispr/cas Toolboxmentioning
confidence: 99%
“…Gilbert et al compared different repressive effector domains, including the KRAB (Krüppel associated box) domain, the WRPW domain and the CS (Chromo Shadow) domain, and found that dCas9-KRAB was the best repressor when targeting to a window of -50 to +300 bp relative to the transcription start site (TSS), or 0–100 bp region just downstream of the TSS ( Figure 3C ; Gilbert et al, 2013 , 2014 ). Another dCas9 fusion domain, Mxi1, a mammalian transcriptional repressor domain that is reported to interact with the histone deacetylase Sin3 homolog in yeast, also showed effective repression in yeast ( Gilbert et al, 2013 ; Jensen et al, 2017 ; Schwartz et al, 2017 ; Geller et al, 2019 ; Wensing et al, 2019 ). In another research, KRAB was fused to RNA-binding domains (COM-KRAB) and achieved similar repression effects when targeting DNA sites overlapped the TSS using a scaffold RNA (scRNA) ( Figure 3D ; Zalatan et al, 2015 ).…”
Section: Regulation Of Gene Expression By Crispr/cas Toolboxmentioning
confidence: 99%
“…The faster and cheaper genetic manipulation of fungal genome and expression facilitated by CRISPR-Cas9 is likely to have a profound impact on medical mycology. Loss of function, gene activation, and gene inhibition strategies can be scaled up as CRISPR-Cas9 libraries [95][96][97], and large-scale library screens can facilitate the identification of new targets for antifungal therapy, of which there is a desperate need [98].…”
Section: Perspectives and Future Directionsmentioning
confidence: 99%
“…Wensing and colleagues also developed an improved dCas9 system fused with codon optimised repressor domain of mammalian repressor Mxi1. The authors established an efficient and scalable CRISPR-interference (CRISPRi) system for C. albicans which when paired with corresponding guide RNA, can allow repression of the desired gene [34].…”
Section: Crispr/cas Gene Editingmentioning
confidence: 99%